MARKETING COMMUNICATION STRATEGY OF JAMU IBOE PRODUCT USING OMNI-CHANNEL AND BRAND REPSOSITIONING IN TARGETING MILLENIAL CONSUMERS - Wulandari, Vivi Pramitha (The Commercium, 2022)
This research examines the success of an herbal medicine product in millennial consumers. The purpose of this study is to find out how the strategy carried out by PT. Jamu IBOE Jaya through the OMNI-CHANNEL strategy and brand repositioning in targeting millennial generation consumers. The background of this research is that jamu, which is one of Indonesia’s cultural heritage, has experienced a decline in sales among millennials because of the public perception that jamu is a bitter, unpalatable, and ancient product. Based on these problems, researchers are interested in knowing how the marketing strategy in Jamu IBOE through OMNI-CHANNEL and brand repositioning at PT. Jamu IBOE Jaya in targeting millennial consumers and how the millennial community perceives herbal products today. The research method used is qualitative with a case study approach. The results of the research obtained showed that the marketing strategy of herbal medicine to millennial consumers used by PT. Jamu IBOE Jaya is through the OMNI-CHANNEL strategy and brand repositioning to change people’s perceptions of the image of jamu. So that a new perspective will be created for herbal medicine from the millennial generation. Keywords: Marketing Communication, OMNI-CHANNEL, Brand Repositioning, Traditional Herbal Medicine, Millennial community perspective